THE DEVELOPMENT ACTIVE LEARNING ACTION LEARNING STRATEGY ORIENTED TEACHING LEARNING MATERIALS ON ECOSYSTEM IN GRADE VII JUNIOR HIGH SCHOOL - SURYANING K, IRMA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
The objective of this research were to develop teaching learning materials, to describe the feasibility of teaching learning materials, and to describe the response of students about teaching learning materials oriented active learning action learning strategy on ecosystem. This research was a development research of teaching learning materials using four-D models. The development of teaching learning materials result tested finitely to 15 students in MTS Al Fatich Surabaya. Parameter that measured are the feasibility of teaching learning materials, and student’s response. Data analized in quantitative descriptive. Based on the results of the validation, teaching learning materials includes student worksheets and book are feasible and get percentage in series 85,09% and 85,97% with very proper criteria and get positive response from students that showed with percentage of students response to students book and student’s worksheet in series 90,3% and 86,7%. Key Words: teaching learning materials, active learning action learning strategy, ecosystem.